2011
DOI: 10.4103/0970-9185.83680
|View full text |Cite
|
Sign up to set email alerts
|

Pre-induction low dose pethidine does not decrease incidence of postoperative shivering in laparoscopic gynecological surgeries

Abstract: Objectives:The incidence of shivering in patients undergoing a laparoscopic procedure is stated to be about 40%. A majority of laparoscopic gynecological procedures are taken up on an outpatient basis. Postoperative shivering may delay hospital discharge and is a common cause of discomfort in patients recovering from anesthesia.Aims:To determine the effect of pre-induction, low-dose pethidine on postoperative shivering in patients undergoing laparoscopic gynecological surgeries.Setting and Design:Sixty females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Bhukal et al . [ 15 ] concluded that prophylactic pre-induction use of low dose pethidine does not have major role in preventing postoperative shivering. Furthermore Zahedi[ 16 ] observed superiority of tramadol to pethidine in preventing shivering, due to its earlier onset of action, less untoward consequences and its higher safety when used as an analgesic in the hands of nonanesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Bhukal et al . [ 15 ] concluded that prophylactic pre-induction use of low dose pethidine does not have major role in preventing postoperative shivering. Furthermore Zahedi[ 16 ] observed superiority of tramadol to pethidine in preventing shivering, due to its earlier onset of action, less untoward consequences and its higher safety when used as an analgesic in the hands of nonanesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (9) found an association between the increased incidence of nausea and vomiting by adding meperidine to subarachnoid administered bupivacaine, and also by higher doses of intrathecal meperidine (25 mg) in comparison to a lesser dose (12.5 mg). Bhukal et al (13) showed that the incidence of shivering was lower in the meperidine 0.5 mg/kg than 0.3 mg/kg but none of these doses of meperidine had a statistically significant adverse effect on patients, compared with placebo. Results of these aforementioned studies are in contrast with our results.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Khan et al (9) rejected the use of intrathecal meperidine because of increased incidence of nausea and vomiting. This controversy about usefulness and side effects of intrathecal meperidine or morphine is continued in other studies (10)(11)(12)(13), which makes it necessary to conduct further studies.…”
Section: Introductionmentioning
confidence: 99%
“…In another similar study by Wason et al, prophylactic ketamine had no superior effect to clonidine and tramadol in controlling and decreasing POS (Wason, Jain, Gupta, & Gogia, 2012). Interestingly, unlike clonidine in our study, Bhukal et al showed that low dose pethidine does not decrease incidence of postoperative shivering in laparoscopic surgeries (Bhukal, Solanki, Kumar, & Jain, 2011). Recent publications have mentioned effect of preemptive Dopamine antagonist such as ondancetrone and granicetrone in decreasing post-operative shivering (Sagir et al, 2007;Teymourian et al, 2015).…”
Section: Resultsmentioning
confidence: 37%